Development of Interactive Multimedia Using Adobe Animate Software on the Material of Sequences and Series For Class XI MAN Bintan - Arie Setiawan; Okta Alpindo; Puji Astuti (Jurnal Gantang, 2022)
In the implementation of the teaching and learning process, the use of learning media is still not optimally applied, besides seeing the obstacles experienced by students in learning mathematics, especially the material for rows and Series. So, a solution is needed to deal with the problems that occur. Based on the results of interviews conducted with a mathematics subject teacher, it was found that the teaching materials required by students to support mathematics learning with the demands of the use of technology were in the form of teaching materials that could be run on a computer or smartphone. This study aims to describe the development of learning media in the form of interactive multimedia using Adobe Animate on the material of sequences and Series for class XI Islamic High School (MAN) Bintan, which is valid and practical. The type of research used is Research and Development (R&D) using the ADDIE research model, which stands for Analysis, Design, Development, Implementation, and Evaluation; in this current research, it was only until the implementation stage. The subjects of this study were 20 students of class XI MAN Bintan. The types of data in this study are quantitative and qualitative data. Research instruments are media and material validation sheets and questionnaires for teacher and student responses to be checked for practicality. The results showed: (1) the validity of interactive multimedia based on the assessment of media and material experts got an average percentage of 81,37% validity with very valid criteria. (2) the practicality of interactive multimedia based on the questionnaire responses of teachers and students after using interactive multimedia got an average percentage of 89,34% practicality with very practical criteria.